THE USE OF FIGURATIVE DEVICES IN THE SPEECH OF STORY CHARACTERS - Go‘zal Saliyevna Matyakubova (International Journal of Literature and Language Studies, 2026)
This article analyzes the figurative devices characteristic of characters’ speech based on the stories of Khayriddin Sulton. It reveals the writer’s mastery in using tropes and creating vivid character portrayals through speech.